Assessing behavioral determinants of sharia gold investment intention: The roles of literacy, motivation, inclusivity, and risk perception - Angeline Natama Silaban; Vina Ashima Fibranawa; Ahmad Rabbani Zainudin (Journal of Economic, Business & Accounting Research, 2026)
Background: Indonesia has the second-largest Muslim population in the world, which provides a strong potential for the development of its sharia economy. However, in 2024, levels of sharia financial literacy and inclusivity remain low, with inclusivity lagging behind literacy. At the same time, sharia gold investment among young people is experiencing significant growth. This study aims to examine the influence of Islamic economic literacy, motivation, financial inclusivity, and risk perception on students’ interest in sharia gold investment at Universitas Gadjah Mada. Methods: This research applies a quantitative survey approach using a structured questionnaire with a five-point Likert scale. A total of 174 students were selected using purposive sampling. The data were analyzed using ordered logit regression with robust standard errors to determine which factors significantly affect students’ investment interest. Findings: The results show that Islamic economic literacy, motivation, financial inclusivity, and risk perception collectively influence students’ interest in sharia gold investment. However, only Islamic economic literacy and motivation have statistically significant positive effects, while financial inclusivity and risk perception do not show significant influence in the regression model. Conclusion: Improving Islamic economic literacy and strengthening students’ motivation are the most effective strategies to increase interest in sharia gold investment among young people. Novelty/Originality of this article: This study offers a comprehensive explanation of early-stage investment behavior by combining empirical survey data with inferential analysis, providing insights into the factors driving sharia investment interest in Indonesia’s developing Islamic finance market.